Pre-Service Teachers’ Perception of Online Teaching and Learning During the COVID – 19 Era - Naah, Anna Mwinbuabu (International Journal of Scientific Research and Management (IJSRM), 2020)
The disclosure of COVID – 19 saw an increasing popularity of Information technology. Most of the educational institutions has resort to online teaching and learning. The purpose of the study was intended to find out pre-service teachers’ perception of online teaching and learning during the COVID – 19 era. In this study, a quantitative descriptive survey research design was adopted. The research instrument that was used to collect the data was questionnaire. The items on the instrument that is the questionnaire were self-developed by the researcher for this study. The non-probability sampling technique namely purposive sampling was employed to select the respondents from Offinso College of Education in the Ashanti Region. A total of 94 pre-service teachers participated in the study. Out of this total, 49 females and 45 males, were pre-service teachers’ trainees on a 4-year Bed Primary Education Programme pursuing General Chemistry as one of their core courses.The results from the study showed that most of the pre-service teachers’ had an idea of the units taught for the semester. Pre-service teachers’ expressed great need for lessons to be delivered using video and audio as it makes lesson real and also see their tutor even though it required much data to access video. The pre-service teachers’ expressed great interest in tutors using trial questions and quiz in assessing them and responds from assessment should be submitted through what’s up platform. With all the challenges pre-service teachers’ encountered during online teaching and learning they appreciated the tutor-learner relationship and interactions as cordial, collaborative and done in a form of discussion. It is therefore recommended that there should be stable network connectivity and subside on data bundle for learners.